The Effect of Diabetes Mellitus on Total Ankle Arthroplasty Outcomes - Jordan A. Helbing BS; Benjamin Farley MD; Alex Gu MD; Gautam Siram; Benjamin Stein MD; Marc David Chodos MD (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis; Ankle Introduction/Purpose: The utility of total ankle arthroplasty (TAA) for management of end-stage ankle arthritis continues to increase. Postoperative infection after TAA is a devastating complication leading to additional surgeries, hospitalizations, long term antibiotics, arthrodesis, and sometimes amputation. Diabetes has been shown to be associated with postoperative infections following other orthopedic procedures. While the majority of literature demonstrates an association between diabetes and post- operative complications following TAA, other studies have demonstrated no such association. The goal of this study was to determine if diabetes influences the outcomes following TAA. Methods: An insurance database was utilized to identify patients undergoing TAA for end-stage ankle arthritis with a concurrent diagnosis of diabetes based on CPT, ICD-9, and ICD-10 diagnosis and procedure codes from 2010 to 2021. The postoperative outcomes of all cause revision, periprosthetic joint infection, periprosthetic joint infection with revision, and aseptic revision were compared between diabetic and nondiabetic patients with a minimum 2-year follow up using Kaplan-Meier and Cox proportional hazards analyses. Patient demographics, comorbidities, and Charlson Comorbidity Index was queried and analyzed via univariate and multivariate analysis, along with 90-day postoperative outcomes. Results: The study population included 8,317 patients who underwent TAA, 345 of which had a concurrent diagnosis of diabetes, with a minimum of 2-year follow up from 2010 to 2021. After multivariate Cox proportional hazards analysis, the 5-year cumulative incidence of PJI was 7.3% in diabetic patients compared to 3.9% in nondiabetic patients, with a 95% increased risk of revision (HR 1.95, 95% CI: 1.15-3.30, P=0.01). Diabetic patients also demonstrated a 5-year cumulative incidence of septic revision rate of 1.4% compared to 0.4% in nondiabetic patients, with a 363% increased risk (HR 4.63, 95% CI: 1.22-17.52, P=0.02). After controlling for differences in demographics and comorbidities through multivariate analysis, diabetes was independently associated with an increased risk for stroke (OR 10.12, P=0.007). Conclusion: The incidence of post-operative complications, including increased risk of 5-year risk of periprosthetic joint infection and septic revision was higher among diabetic patients compared to nondiabetic patients.